PENGARUH LEVERAGE, PROFITABILITAS DAN UKURAN PERUSAHAAN TERHADAP AGRESIVITAS PAJAK (Studi Empiris Perusahaan Plastik dan Kemasan Yang Terdaftar Di BEI Periode 2016-2020) - Emi Masyitah; Eka Purnama Sari; Anggraini Syahputri; Julyanthry Julyanthry (ITB AAS INDONESIA, 2022)
This study aims to determine the effect of leverage, profitability and company size on tax aggressiveness. The population in this study is all companies registered in the IDX plastic and packaging sub-sector during the research period: 2016-2020. The sampling technique used is purposive sampling. The samples obtained were 6 companies, with a total of 30 observations. The finding is that there is no significant influence between leverage, profitability and the size of the company on tax aggressiveness. Leverage, profitability and the size of small or large enterprises do not affect management to carry out tax aggressiveness.